2017
DOI: 10.1111/ajt.14284
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Markers of Fibrosis and Risk of Cardiovascular Events and Death in Kidney Transplant Recipients: The FAVORIT Trial

Abstract: Cardiovascular risk remains high in kidney transplant recipients (KTRs) despite improved kidney function after transplant. Urinary markers of kidney fibrosis and injury may help to reveal mechanisms of this risk. In a case-cohort study among stable KTRs who participated in the FAVORIT trial, we measured 4 urinary proteins known to correlate with kidney tubulointerstitial fibrosis on biopsy (urine alpha 1 microglobulin [α1m], monocyte chemoattractant protein-1 [MCP-1], procollagen type I [PINP] and type III [PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 39 publications
(79 reference statements)
3
26
0
Order By: Relevance
“…Moreover, the increased expression and deposition of collagen type I alpha 1 in interstitial kidney fibrosis can be attributed to increased expression of procollagen-n-proteinase as it has been shown in the spontaneously hypertensive rat [87]. High levels of urinary procollagen type I have been associated with both cardiovascular disease and death in kidney transplant recipients [88]. Despite that, the importance of procollagen I alpha 1 excretion in urine as a marker of kidney disease progression has not been yet thoroughly evaluated in long prospective large cohorts of patients with CKD.…”
Section: Procollagen I Alphamentioning
confidence: 87%
“…Moreover, the increased expression and deposition of collagen type I alpha 1 in interstitial kidney fibrosis can be attributed to increased expression of procollagen-n-proteinase as it has been shown in the spontaneously hypertensive rat [87]. High levels of urinary procollagen type I have been associated with both cardiovascular disease and death in kidney transplant recipients [88]. Despite that, the importance of procollagen I alpha 1 excretion in urine as a marker of kidney disease progression has not been yet thoroughly evaluated in long prospective large cohorts of patients with CKD.…”
Section: Procollagen I Alphamentioning
confidence: 87%
“…Monocyte chemoattractant protein-1 (MCP-1) is a chemokine that attracts macrophages to the site of injury [15][16][17], whereas chitinase-3-like protein-1 (YKL-40) functions as a mediator of the reparative response to tubular injury [18,19]. Some studies have demonstrated that urinary markers of tubular damage are associated with higher cardiovascular and mortality risks [17,[20][21][22], whereas other studies found no significant associations [23,24]. Few of the existing studies included large numbers of participants with CKD who may have more extensive tubule damage and higher risk for CVD and death.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the potential association between serum T50 and the composite CVD outcome, we utilized an efficient, preexisting case-cohort selection scheme employed for prior FAVORIT ancillary studies [11][12][13], especially the report of Park et al [13]. Briefly, a 530-participant subcohort with complete baseline data for key laboratory variables, including serum creatinine and lipid studies, as well as urine albumin to creatinine ratio (UACR), was selected at random from the entire cohort, regardless of whether or not the T50, Fetuin-A, and CVD in Kidney Transplantation participants had experienced a fatal or nonfatal CVD outcome during follow-up [11][12][13].…”
Section: Study Populationmentioning
confidence: 99%
“…Briefly, a 530-participant subcohort with complete baseline data for key laboratory variables, including serum creatinine and lipid studies, as well as urine albumin to creatinine ratio (UACR), was selected at random from the entire cohort, regardless of whether or not the T50, Fetuin-A, and CVD in Kidney Transplantation participants had experienced a fatal or nonfatal CVD outcome during follow-up [11][12][13]. We also selected all participants in the full cohort who were identified as having experienced a CVD event, irrespective of whether they were sampled in the random subcohort.…”
Section: Study Populationmentioning
confidence: 99%